2008
DOI: 10.1175/2007jas2194.1
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of West African Dynamics Using a Linearized GCM*

Abstract: This study utilizes a linear, primitive equation spherical model to study the development and propagation of easterly wave disturbances over West Africa. Perturbations are started from an initial disturbance consisting of a barotropic vortex and the governing equations are integrated forward in time. The perturbations are introduced into basic states corresponding to the observed dynamical and thermodynamical characteristics of two wet years in the Sahel and two dry years.The model simulations show consistent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 64 publications
1
21
0
Order By: Relevance
“…This permits the development of waves on the TEJ. Such waves have been observed over West Africa [135] and their characteristics match those predicted by a numerical simulation of African wave activity [136]. Such waves may play a role in the development of extreme precipitation events in the western Sahel.…”
Section: Tropical Easterly Jetsupporting
confidence: 60%
See 3 more Smart Citations
“…This permits the development of waves on the TEJ. Such waves have been observed over West Africa [135] and their characteristics match those predicted by a numerical simulation of African wave activity [136]. Such waves may play a role in the development of extreme precipitation events in the western Sahel.…”
Section: Tropical Easterly Jetsupporting
confidence: 60%
“…The predicted waves are of planetary scale with a period of 5 to 6 days and they develop to the northwest of the mid-level AEW. Observations showed that such a wave developed in July of 1950, a very wet year (Nicholson et al [136], with characteristics similar to the predicted TEJ waves. Potential vorticity theory suggests that the waves on the TEJ develop via interactions between the surface and the TEJ.…”
Section: Wave Activity and Links To Convectionmentioning
confidence: 75%
See 2 more Smart Citations
“…This location most commonly produces the configuration of rainfall anomalies represented by a dipole in which the Sahel is anomalously wet and the Guinea Coast is anomalously dry. As noted in Section 2.2, strong, deep and extensive equatorial westerlies and a strong vertical shear zone over the Sahel characterize the Sahel mode Nicholson et al, 2007). The shear indicates that baroclinic instability is probably important in the Sahel in the wet years.…”
Section: A New Paradigmmentioning
confidence: 79%